Torsion of Atypical Meckel’s Diverticulum Treated by Laparoscopic-Assisted Surgery - Atsushi Kohga; Kimihiro Yamashita; Yuto Hasegawa; Kiyoshige Yajima; Takuya Okumura; Jun Isogaki; Kenji Suzuki; Akihiro Kawabe; Akira Komiyama (Case Reports in Medicine, 2017)
Introduction. Meckel’s diverticulum (MD) is the most common congenital anomaly of the intestine, with an incidence of 2~4%. Of those, only 2% of patients with MD are symptomatic. Torsion of MD is extremely rare, and only a dozen cases have been previously reported. Case Report. The patient was a 49-year-old male who presented to our emergency room with a chief complaint of lower abdominal pain. Computed tomography imaging revealed an irregular polycystic mass connected to the small intestine that measured 7.5 cm in a diameter. A laparoscopic-assisted partial resection of the jejunum was performed. The lesion was found to have caused torsion and was located 130 cm from the ileocecal valve. The specimen was polycystic in appearance and showed communicating links with the submucosal layer of jejunum but not with the lumen. The pathological diagnosis was a torsion of an atypical presentation of MD. Conclusion. This case was different from typical cases of MD in that it was located on significantly oral side and had the appearance of polycystic morphology.